EFFECTIVENESS OF PEER GROUP SUPPORT IN THE APPLICATION OF ACUPRESSURE AND ABDOMINAL STRETCHING ON MENSTRUAL PAIN IN ADOLESCENT FEMALES WITH THE SELF DETERMINATION MODEL - Mahundingan, Rosari Oktaviana; Andriani, Dewi; Ramadhani, Dwi Yuniar (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: One of the changes that appears in adolescent is menstruation. One way to reduce menstrual pain is to use relaxation techniques, acupressure, and abdominal stretching. Another way is to help teenagers deal with pain by using group methods, such as peer group support. Objective: The purpose of this study was to determine the relationship between Peer Group Support in the application of acupressure and abdominal stretching to menstrual pain in adolescent girls using the self-determination model approach. Methods: This study used a quasi-experimental design with a pre-test and post-test design. The sampling technique used was simple random sampling. Inclusion criteria were respondents who had menstruated, experienced menstrual pain, aged at menarche between ≤12 years to ≥14 years, and had a menstrual duration of 7 days, as well as being cooperative and willing to be a respondent. The sampling technique used was simple random sampling. The sample size was 70 female adolescent respondents. Results: The results of the study with Paired t-test showed that the Acupressure and Abdominal Stretching intervention groups both experienced changes with a value of p = 0.03 in the Acupressure and Abdominal Stretching groups and p = 0.000. On average, there was an increase in overcoming menstrual pain, but in the Acupressure group, there was only a slight increase in the t-count, which was 2.45. In the abdominal stretching group, the t-count value was greater, at 11.16. Conclusion: The published research shows that acupressure and abdominal stretching were also carried out on the same group in the 2 intervention groups. The results were effective and could be carried out together, as evidenced by a decrease in the level of pain during menstruation and self-determination.